Adrenal incidentaloma caused by extramedullary haematopoiesis: conservative management is optimal - Sekar, Suganya (BMJ Case Rep, 2015)
We present a thalassaemic patient with extramedullary haematopoiesis in the adrenal gland, which is one of the rare sites of involvement. A 29-year-old man presented with a history of anaemia since childhood which required blood transfusion recently. On examination, he had pallor, icterus and splenomegaly with no other palpable abdominal mass. He was diagnosed to have β-thalassaemia. Ultrasonography of the abdomen showed an incidental right adrenal mass with splenomegaly; CT revealed a large right adrenal mass with heterogeneous density. Adrenal adenoma, carcinoma and extramedullary haematopoiesis were considered in the differential diagnosis. After excluding a functioning tumour, the diagnosis was confirmed by ultrasound-guided biopsy. Since the patient was asymptomatic, the adrenal lesion was managed conservatively.